'Does the form of this word fit its meaning?' The effect of learner-generated mapping elaborations on L2 word recall. (January 2017) - Deconinck, Julie; Boers, Frank; Eyckmans, June
If known words can be defined psycholinguistically as 'form–meaning mappings', the present article investigates whether prompting learners to evaluate whether the form of a new second language (L2) word fits its meaning generates 'mapping elaborations' that aid recall. Thirty Dutch-speaking upper-intermediate learners of English were invited to rate and motivate the degree of congruency they perceived between the form and meaning of 14 novel L2 words. Their ability to recall the form and the meaning of the target words was measured in an unannounced post-test. Recall was found to be positively related to the number of learner-generated mapping elaborations triggered by the task. Elaborations of a sound–symbolic nature appeared particularly useful for rendering the form of new words memorable.